Preoperative fasting hyperglycemia is an independent prognostic factor for postoperative survival after gallbladder carcinoma radical surgery - Zheng P; Wang X; Hong Z; Shen F; Zhang Q (Cancer Management and Research, 2019)
Peng Zheng,1,* Xiaoqian Wang,2,* Zhong Hong,1 Feixia Shen,2 Qiyu Zhang3 1Department of Hepatobiliary Surgery, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, China; 2Department of Endocrinology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, China; 3Department of Hepatobiliary Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, China *These authors contributed equally to this work Background: Preoperative high blood glucose levels are closely associated with poor performance and high mortality in cancer patients. This study was designed to investigate the relationship between preoperative fasting hyperglycemia and the prognosis of patients with gallbladder cancer (GBC) after undergoing GBC radical surgery.Patients and methods: A retrospective analysis of 83 eligible patients who underwent GBC radical surgery between 2007 and 2016 was performed. Factors affecting overall survival (OS) and recurrence-free survival (RFS) were analyzed by univariate and multivariate analyses.Results: Of the 83 patients, 35 (42.2%) had preoperative fasting hyperglycemia. The median OS of the enrolled patients was 12 months. The median OS in patients with fasting hyperglycemia before surgery was 18 months, which was shorter than for patients with normal fasting blood glucose levels before surgery (47 months, P<0.001). Preoperative fasting hyperglycemia was associated with shorter survival times in univariate analyses (HR, 3.215; 95% CI, 1.846–5.601; P<0.001). Multivariate analysis showed that patients with preoperative fasting hyperglycemia had a lower OS (HR, 2.832; 95% CI, 1.480–5.418; P=0.002) and RFS (HR, 2.051; 95% CI, 1.127–3.733; P=0.019) than patients with normal preoperative fasting blood glucose levels.Conclusion: Preoperative fasting hyperglycemia is an independent indicator of poor prognosis in GBC patients after GBC radical surgery. Keywords: fasting hyperglycemia, gallbladder carcinoma, GBC radical surgery, prognosis